Sulfur@metal cotton with superior cycling stability as cathode materials for rechargeable lithium–sulfur batteries - Zhang, J.; Ma, Z.; Cheng, J.; Wang, Y.; Wu, C.; Pan, Y.; Lu, Chunsheng (Elsevier, 2015)
Lithium–sulfur (Li–S) batteries have great potential for some high energy applications such as electric vehicles and smart grids due to the high capacity, natural abundance, low cost and environmental friendliness of sulfur. In this work, we use the metal cotton to absorb sulfur firmly as cathode material for Li–S batteries. The as-designed sulfur@metal cotton (S@MC) composite shows a good cycling stability and rate capability. The capacity is retained at 480 mA h g−1 at 0.1 C after 200 cycles. Furthermore, for higher rates, the S@MC cathode material also exhibits stable capacity during different periods.